Corporate Mobility in Krakow and Its Reporting Challenges. A Framework for Analysis - Ewa SLEZAK; Katarzyna SWIETLA (Communications of International Proceedings, 2020)
The present phase of capitalism rests heavily on the internationalization of economic entities. Transnational companies are spreading their activity across the world with the use of outsourcing and offshoring. Hence, transnational corporations are building dense networks of connections and fragment their chains of production across national borders. Human capital is a type of resource that attracts their attention to locate their business in a given place. Along with capital there comes a movement of people, either sent by companies to protect their interests or those who or individually initiate their employment in a given place outside their country of origin. These migrants are the most numerous, but also others move to cities and regions which provide various career opportunities. Krakow serves an interesting example of such as city, a major regional seat for provision of new business services. No doubt, the ideas of global economy materialize here leading to the emergence of a cosmopolitan hub hosting professionals of various nationalities and origin. Sadly, the present state of research on mobility and migration misses an important aspect, i.e. we do not know the extent of mobility and costs associated. The available reporting practices neglect those aspects. This paper focuses on corporate mobility in the context of globalization; the former is materialized by outsourcing and offshoring. By referring to the situation in Krakow, the paper aims at elucidating the transnational dimensions of mobility and attempts to lay grounds for its reporting, both financial and non-financial.
Keywords: Outsourcing; Corporate Mobility; Highly Skilled Migrants; Financial Reporting.